In Vitro and In Vivo Effects of Norathyriol and Mangiferin on α-Glucosidase - Zhi-Long Shi (Biochemistry Research International, 2017)
Norathyriol is a metabolite of mangiferin. Mangiferin has been reported to inhibit α-glucosidase. To the best of our knowledge, no study has been conducted to determine or compare those two compounds on inhibiting α-glucosidase in vitro and in vivo by far. In this study, we determined the inhibitory activity of norathyriol and mangiferin on α-glucosidase in vitro and evaluated their antidiabetic effect in diabetic mice. The results showed that norathyriol inhibited α-glucosidase in a noncompetitive manner with an IC50 value of 3.12 μM, which is more potent than mangiferin (IC50 = 358.54 μM) and positive drug acarbose (IC50 = 479.2 μM) in the zymological experiment. Both of norathyriol and mangiferin caused significant (p<0.05) reduction in fasting blood glucose and the blood glucose levels at two hours after carbohydrate loading and it was interesting that mangiferin and norathyriol can make the decline of the blood glucose earlier than other groups ever including normal group in the starch tolerance test. However, norathyriol and mangiferin did not significantly influence carbohydrate absorption in the glucose tolerance test. Therefore, the antidiabetic effects of norathyriol and mangiferin might be associated with α-glucosidase, and norathyriol was more potent than mangiferin.